The Relationship Between System Involvement and Vitamin D Level in Cases Diagnosed with Multisystem Inflammatory Syndrome in Children - Aysun Soyugüzel; Ayşegül Bükülmez; Ayhan Pektaş; İbrahim Eker; Mehmet Çeleğen; Hilal Koyuncu (Güncel Pediatri)
Introduction: Vitamin D is a steroid prehormone that is produced in the skin as a result of exposure to UV-B, is fat-soluble and has immunomodulatory properties by affecting immune cells. In this study, it was aimed to evaluate the relationship between systemic involvement and 25-OH vitamin D level in patients with a diagnosis of MIS-C. Materials and Methods: It is a descriptive research. It was conducted at AFSÜ, Health Application and Research Center between 01.10.2020-01.04.2022. Patients aged between 1 month and 18 years who were diagnosed with MIS-C and who applied to AFSU, Child Health and Diseases Clinic, and whose serum 25-OH vitamin D was in the electronic archive system, were included in this study. The collected data were analyzed with the Statistical Package for Social Sciences version 26.0. It was done with the S package program.Since vitamin D was not distributed normally, the Mann-Whitney U test was used when comparing between paired groups. The Kruskal Wallis test was used when comparing vitamin D levels between more than two groups. Results: This retrospective study was conducted with 34 patients diagnosed MIS-C. The mean age of the cases was 7.03±3.9 years; 52.9% (n=18) were males and 47.1% (n=16) were females. Gastrointestinal system (58.8%; n=20), cardiac (64.7%; n=22) and neurological involvement (23.5%; n=8) were found. Mean 25-OH vitamin D were found to be 15.7 (IQR= 18) ng/mL in gastrointestinal system, 16.8 (IQR=17) ng/mL in cardiac, and 12 (IQR= 8) ng/mL in neurological system involvement. No statistically significant differences were found between systemic involvement of the cases and their 25-OH vitamin D (p values: 0.779, 0.957, 0.144, respectively). A negative correlation was found between 25-OH vitamin D of the cases and their age (r=-0.414; p=0.015). When the relationship between 25-OH vitamin D and fibrinogen in patients diagnosed with MIS-C was evaluated, a negative correlation was also found (r=-0.414; p=0.015). Conclusion: As a result, mean 25-OH vitamin D levels in cases diagnosed with MIS-C were found to be at an insufficient level. It was suggested that prophylactic vitamin D should be administered in children. In addition, no significant difference was found between system involvement and vitamin D level.